Beyond pity and inspiration a critical discourse analysis on the representation of children with disabilities in Maalaala mo Kaya - Buensuceso, Era Cassandra Valdez
This study examined the representation of children with disabilities (CWDs) in the Philippine TV drama anthology program, Maalaala Mo Kaya (MMK). Utilizing the framework of Critical Discourse Analysis (CDA) and Critical Disability Theory (CDT), the study aimed to problematize the construction of disability in the media and explore the societal influences and power dynamics shaping these representations. Applying the principles of CDT, the study sought to understand how societal constructions and power dynamics influence disability portrayals at the textual, discursive and social levels of discourse practice. The findings highlighted both outdated and nuanced representations of disability among CWDs, revealing discursive practices that either reinforced or challenged ableist norms within MMK. One notable finding was the prevalence of portraying disability as a divine punishment, shedding light on the religious inclinations of Filipinos. This research contributes to the understanding of disability representations in local media and advocates for inclusivity and the empowerment of CWDs.